2016
DOI: 10.5812/rijm.43217
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Simultaneous Usage of Bevacizumab and Silicone Oil Injection After Vitrectomy in Diabetic Tractional Retinal Detachment

Abstract: Background: Tractional retinal detachment (TRD), a major vision threatening complication, is one of the most common eye emergencies. The most common cause of TRD is proliferative diabetic retinopathy (PDR). The aim of this study was to evaluate the effect of simultaneous usage of bevacizumab and silicone oil injection after vitrectomy for the treatment of diabetic tractional retinal detachment Methods: Twenty five patients (25 eyes) with severe proliferative diabetic retinopathy were recruited into the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Intravitreal injections are not usually performed in an SO-filled eye, as the effective concentration of injected substances is unpredictable in such eyes [ 9 ]. However, triamcinolone acetonide [ 10 , 33 ], dexamethasone implant [ 34 ], and bevacizumab [ 12 , 13 , 14 ] have been injected in SO-filled eyes to improve surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravitreal injections are not usually performed in an SO-filled eye, as the effective concentration of injected substances is unpredictable in such eyes [ 9 ]. However, triamcinolone acetonide [ 10 , 33 ], dexamethasone implant [ 34 ], and bevacizumab [ 12 , 13 , 14 ] have been injected in SO-filled eyes to improve surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of satisfactory results following intravitreal triamcinolone acetonide injection [ 10 ] and the injection of VEGF inhibitors [ 11 , 12 , 13 ] into an SO-filled eye. In addition, Alishiri et al [ 14 ] recently reported favorable results with the simultaneous usage of bevacizumab and SO following a vitrectomy in diabetic patients with TRD. However, in some cases, after SO injection in PDR surgery, macular edema remains in SO-filled eyes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 In this case, the clinical success of the peri-operative or post-operative application of humanized anti-VEGF monoclonal antibody into the SiO-filled eyes has been shown in previous studies. [8][9][10][11][12] More specifically, Avastin® injection into the SiO-filled eye is a safe and effective method in the management of "neovascular iris" and "neovascular glaucoma" seen after the vitrectomy surgery of advanced proliferative diabetic retinopathy cases. [10][11][12] However, some concerns regarding applying Avastin®to the SiO tamponade-filled eyes have been noted in the literature.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] More specifically, Avastin® injection into the SiO-filled eye is a safe and effective method in the management of "neovascular iris" and "neovascular glaucoma" seen after the vitrectomy surgery of advanced proliferative diabetic retinopathy cases. [10][11][12] However, some concerns regarding applying Avastin®to the SiO tamponade-filled eyes have been noted in the literature. The drug delivery of Avastin® or its local concentration may become unpredictable when injected into the SiO tamponade-filled eyes.…”
mentioning
confidence: 99%